Communication and Civil Service Delivery in Benue and Kwara States, Nigeria - Awotunde, Taiye Adewale (Journal of Technology Management and Business, 2024)
Communication is an important aspect of a country’s political, social and economic development. Communication as an environmental factor developed with the evolution of man and this was through simple signs and gestures. Technological development brought about improvement in communication over time. Communication impacts service delivery in the civil service in Benue and Kwara States, Nigeria. The study was anchored on the communication theory. The methodology adopted by the study was the survey research design. The sampling technique that was adopted for the study is the stratified random technique. The population of the study was one thousand, four and thirty-nine ((1,439). The sample size for the study was three hundred and thirteen (313). Stratified random sampling technique was used for the selection of the respondents. The study revealed that communication had significant influence on service delivery F(1,304) = 81.320, p < 0.05). The study concluded that, communication in organisation had significant and positive effect on service delivery in Benue and Kwara States of Nigeria. The study recommends that communication in Benue and Kwara States, civil services should be improved upon in order to make for a virile and dynamic civil service in the concerned states.